The fibres with fluoro-edenitic composition in Biancavilla (Sicily, Italy): health impact and clues for environmental remediation - Pietro Comba; Salvatore Scondotto; Loredana Musmeci
Subsequently to the observation of a localized excess of mortality from malignant pleural neoplasms in the town of Biancavilla (Sicily), previously unknown amphibolic fibres with fluoro-edenitic composition were detected as naturally occurring soil contaminants. Less then two years after the initial report, ISS provided a set of public health recommendations that were complied by regional and local institutions. The recognition of Biancavilla as a National Priority Contaminated Site in 2002 opened the way to clean-up interventions. An up-dating of epidemiological studies, exposure assessment investigations and in vivo and in vitro mechanistic studies on fluoro-edenite fibres is provided in this issue. Scientific evidence can provide a sound foundation to public health action and environmental remediation. Finally, it is now necessary to properly tune the response of the health system to the community needs in terms of diagnostic procedures and medical treatment.